Genetic study of the BRAF gene reveals new variants and high frequency of the V600E mutation among Iranian ameloblastoma patients. (7th November 2017) - Soltani, Maryam; Tabatabaiefar, Mohammad Amin; Mohsenifar, Zhaleh; Pourreza, Mohammad Reza; Moridnia, Abbas; Shariati, Laleh; Razavi, Seyyed Mohammad
Abstract : Background: Ameloblastoma is a benign, slow‐growing and locally invasive tumor. It is one of the most prevalent odontogenic tumors, with an incidence rate of 1% of all oral tumors and approximately 18% of odontogenic tumors. A group of genes have been investigated in patients with ameloblastoma. The BRAF V600E mutation has been implicated as the most common mutation in ameloblastoma. The presence or absence of this mutation has been associated with several clinicopathological properties, including location, age at diagnosis, histology, and prognosis. Although some populations have been investigated so far, little data are available on the Iranian population. The current research was launched to study the BRAF V600E mutation among a cohort of Iranian patients with ameloblastoma. Methods: In this clinicopathological and molecular biology study, a total of 19 formalin‐fixed, paraffin‐embedded tissues were studied. DNA extraction was performed, followed by PCR‐sequencing of exons 10 and 15 of the BRAF gene to identify mutations . In silico analysis was performed for the identified variants. Results were analyzed by T test, Chi‐square, and Fisher's exact test. Results: Totally, 12 of 19 samples (63%) harbored the p. V600E hotspot mutation. In addition, we identified several variants, two of which were novel. The c.1769T>G (p. V590G) and c.1751C>T (p.L584F) as the novel variants showed a possible damaging effect by in silico analysis. No variant was found within exon 10. Conclusions: Our study confirms the role of BRAF mutations in ameloblastoma in the Iranian patients studied.